Purified chick embryo cell rabies vaccine: economical multisite intradermal regimen for post-exposure prophylaxis. - Suntharasamai, P. (Cambridge University Press, 1987)
The standard six-dose intramuscular (i.m.) rabies post-exposure vaccine regimen using a new purified chick embryo cell (PCEC) vaccine was compared with two economical multisite intradermal (i.d.) PCEC regimens, a multisite i.m. PCEC schedule and a subcutaneous regimen using a suckling mouse brain (SMB) rabies vaccine manufactured in Thailand. The neutralizing antibody results for the four-site and eight-site i.d. and the standard i.m. PCEC regimens were similar over 3 months. A three-site i.m. PCEC regimen had no advantage. The SMB vaccine gave the lowest antibody levels. Human rabies immune globulin therapy significantly increased the GMT of all groups on day 7, unlike equine antirabies serum (EARS). Both antisera suppressed antibody responses to PCEC on days 14 and 28. Three generalized reactions probably related to EARS were the only serious side effects. An eight-site i.d. PCEC vaccine regimen proved as immunogenic as the routine i.m. schedule and, if implemented as post-exposure prophylaxis, would be the cheapest widely available tissue culture vaccine regimen. The protective efficiency should now be tested in patients bitten by rabid animals.